Acute gastrointestinal bleeding due to primary aortoduodenal fistula: Report of two rare cases - Ufuk TÜTÜN; Ayşen AKSÖYEK; Ahmet Tulga ULUS; Ali İhsan PARLAR and M. Kamil GÖL and Murat BAYAZIT (Turkish Journal of Gastroenterology, 2019)
-